Does adjustment of GFR to extracellular fluid volume improve the clinical utility of cystatin C?. Issue 6 (1st June 2000) - Kilpatrick, Eric S; Keevil, Brian G; Addison, G Michael
Abstract : BACKGROUND: Cystatin C measurement has been proposed as a replacement for creatinine as a serum measure of glomerular filtration rate (GFR). It has also been suggested that GFR itself should be adjusted to the extracellular fluid volume (ECV) of a child rather than the body surface area (BSA). AIMS: To assess the potential of cystatin C compared to serum creatinine in assessing GFR and to establish whether adjustment of GFR to ECV rather than BSA affects the potential usefulness of cystatin C. METHODS: Cystatin C and plasma creatinine were measured in 64 paediatric patients undergoing 77 51 Cr-EDTA GFR measurements over a six month period. RESULTS: 1/cystatin C concentrations were more closely related to GFR (median 98 ml/min/1.73 m 2, range 8–172) after adjustment for patient BSA ( r  = 0.81 versus r  = 0.44). 1/Creatinine concentrations appeared to be an inferior estimate of BSA adjusted GFR ( r  = 0.41), even following the use of the Schwartz formula ( r  = 0.37). Bland Altman statistics showed cystatin C could still only predict 95% of GFR values to within ±41 ml/min/1.73 m 2 of the 51 Cr-EDTA method. The relation between GFR and 1/cystatin C was not improved by adjusting 51 Cr-EDTA GFR to ECV rather than BSA ( r  = 0.76 versus r  = 0.81). CONCLUSIONS: Cystatin C appears superior to serum creatinine in paediatric subjects although its performance is unlikely to supplant 51 Cr-EDTA GFR measurement. This performance is not being underestimated because of adjusting GFR to BSA rather than ECV.